The Utility of a Wireless Implantable Hemodynamic Monitoring System in Patients Requiring Mechanical Circulatory Support. Issue 3 (May 2018) - Feldman, David S.; Moazami, Nader; Adamson, Philip B.; Vierecke, Juliane; Raval, Nir; Shreenivas, Satya; Cabuay, Barry M.; Jimenez, Javier; Abraham, William T.; O'Connell, John B.; Naka, Yoshifumi
Abstract : Proper timing of left ventricular assist device (LVAD) implantation in advanced heart failure patients is not well established and is an area of intense interest. In addition, optimizing LVAD performance after implantation remains difficult and represents a significant clinical need. Implantable hemodynamic monitoring systems may provide physicians with the physiologic information necessary to improve the timing of LVAD implantation as well as LVAD performance when compared with current methods. The CardioMEMS Heart sensor Allows for Monitoirng of Pressures to Improve Outcomes in NYHA Class III heart failure patients (CHAMPION) Trial enrolled 550 previously hospitalized patients with New York Heart Association (NYHA) class III heart failure. All patients were implanted with a pulmonary artery (PA) pressure monitoring system and randomized to a treatment and control groups. In the treatment group, physicians used the hemodynamic information to make heart failure management decisions. This information was not available to physicians for the control group. During an average of 18 month randomized follow-up, 27 patients required LVAD implantation. At the time of PA pressure sensor implantation, patients ultimately requiring advanced therapy had higher PA pressures, lower systemic pressure, and similar cardiac output measurements. Treatment and control patients in the LVAD subgroup had similar clinical profiles at the time of enrollment. There was a trend toward a shorter length of time to LVAD implantation in the treatment group when hemodynamic information was available. After LVAD implantation, most treatment group patients continued to provide physicians with physiologic information from the hemodynamic monitoring system. As expected PA pressures declined significantly post LVAD implant in all patients, but the magnitude of decline was higher in patients with PA pressure monitoring. Implantable hemodynamic monitoring appeared to improve the timing of LVAD implantation as well as optimize LVAD performance when compared with current methods. Further studies are necessary to evaluate these findings in a prospective manner.